The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Yeast - Industrial Applications 2017
DOI: 10.5772/intechopen.70760
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Ecology of Fermented Table Olives: A Tool for Biotechnological Applications

Abstract: The table olive is considered to be a traditional fermented vegetable in the Mediter ranean countries and its production and consumption is recently spreading all around the world. The presence of yeasts is very important during olive fermentation due to their double role. On one hand, yeasts maintain desirable biochemical activities (lipase, esterase, β-glucosidase, catalase, production of killer factors, etc.) with essen tial technological applications in this fermented vegetable. On the other hand, spoil ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Thus, the subsequent period was Figure 10. Dendrogram generated after cluster analysis of the digitized GTG5-PCR fingerprints of LAB (lactic acid bacteria) strains isolated from AL7 (LAB 6,9), AL8 (LAB 1,2,3,4,5,7,8), and AL9 (LAB 10,11,12,13,14,15,16,17) brine samples at 120 days of fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the subsequent period was Figure 10. Dendrogram generated after cluster analysis of the digitized GTG5-PCR fingerprints of LAB (lactic acid bacteria) strains isolated from AL7 (LAB 6,9), AL8 (LAB 1,2,3,4,5,7,8), and AL9 (LAB 10,11,12,13,14,15,16,17) brine samples at 120 days of fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…The former has been reported in Candida boidinii. Those authors have described the change of free fatty acids' composition of olives that occurred with the yeast inoculum in contrast with sterile conditions, indicating that lipases produced by these microorganisms modify the characteristics of fruit lipids and therefore its organoleptic characteristics [27,30].…”
Section: Discussionmentioning
confidence: 99%
“…The latter is achieved via the capacity of yeasts (1) to degrade several phenolic compounds, which act as inhibitors for LAB growth, and/or (2) to produce several compounds, which are crucial for LAB growth (vitamins, purines, etc.) ( Arroyo-López et al, 2012a ; Anagnostopoulos et al, 2017 ). Thus, nowadays, yeasts are considered an essential part of microbial consortia for succeeding in appropriate olive fermentation.…”
Section: Table Olive Fermentation Microbiotamentioning
confidence: 99%
“…Similarly, although there is a huge number of studies providing the benefits of using yeast starters, either alone ( Ciafardini and Zullo, 2019 ; Schaide et al, 2019 ; Tufariello et al, 2019 ) or in combination with LAB ( Pistarino et al, 2013 ; De Angelis et al, 2015 ; Tufariello et al, 2015 ; Benítez-Cabello et al, 2019a , 2020a ; Chytiri et al, 2020 ; Garrido-Fernández et al, 2021 ), in olive fermentation, the use of yeasts as starters is still at research level ( Table 1 ). The latter strategy seems to be the most promising one, since as previously mentioned, it has been proven that the presence of yeasts favors the growth of LAB population, by (a) degrading complex compounds (e.g., oleuropein and phenolics), which act as inhibitors to LAB, or (b) producing several elements, which are crucial for LAB development (e.g., vitamins and purines) ( Arroyo-López et al, 2012b ; Anagnostopoulos et al, 2017 ). Indeed, De Angelis et al (2015) reported very promising findings by using LAB strains in combination with an autochthonous W. anomalus strain especially regarding the acceleration of the fermentation of Bella di Cerignola table olives.…”
Section: Technological Advancements On Olive Fermentation Processingmentioning
confidence: 99%